Correction: The microbiome in urogenital schistosomiasis and induced bladder pathologies. - Adewale S Adebayo; Mangesh Survayanshi; Shrikanth Bhute; Atinuke M Agunloye; Raphael D Isokpehi; Chiaka I Anumudu; Yogesh S Shouche (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0005826.].